Otomatisasi Sistem Bagasi Terminal Internasional Di Bandar Udara Jenderal Ahmad Yani Semarang - Muliandhi, Puri; Nugroho, Andi Kurniawan; Aji Jr., Edwin Bayu (Fakultas Teknik Elektronika dan Komputer Universitas Kristen Satya Wacana, 2023)
The increasing number of flights proves that the public believes air transportation is one of the most desirable. Of course, the operation of the claim baggage conveyor will increase along with the number of existing passenger luggage. For this reason, the operation of the baggage claim conveyor needs to be done with the help of technology. This research was conducted to assist the work of airline porters, including time and energy efficiency through technology. This tool uses the Arduino Uno microcontroller as the program processing centre. This system will work when the Infrared sensor detects baggage after an x-ray, so the conveyor will be activated automatically. After the conveyor runs, another Infrared sensor will see the baggage on the conveyor. The conveyor will stop automatically when the Infrared sensor does not detect any baggage for a particular time. This tool is equipped with a Push Button so that the baggage claim conveyor can be operated manually and an LCD to explain the instrument's condition and the amount of baggage available. The amount of luggage can be monitored periodically via a smartphone using the ESP8266 WiFi module.